Goat meat production and quality [ - Kadim, I. T. [ (Isam T.)]; Mahgoub, O. [ (Osman)]; Webb, E. C. [ (Edward Cottington)] (CABI, 2011)
Written by some of the world's leading goat meat scientists, and drawing from the most recent publications in the field, this book aims to comprehensively cover the most important areas of goat meat production. Chapters discuss the role of genetics, breding, reproduction, and nutrition in producing good quality, profitable goat meat. The mineral, amino acid and fatty acid composition of goat meat is also addressed, along with a discussion of its nutritive value, aimed at highlighting its health benefits over other red meats.